Critical Geography and the Real World in First-Year Writing Classrooms - Matthew I. Feinberg (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
By helping students confront the ideologies that shape their physical and cultural experiences, critical geography in first year writing classrooms may be one means of collapsing the perceived distance between the classroom and the "real world."